CYCLES AND ANTI-CYCLES OF SOLAR ACTIVITY - Ryabov, M. I. (Одеські астрономічні публікації, 2016)
Currently representation of solar cycles on average monthly data and smoothed values on various indexes from the full solar disk is generally accepted. Such representation creates an illusion of monotone change and perceptions of simultaneity of manifestations of solar activity for all solar disc. At the same time, daily monitoring data reveal the presence of discrete properties of manifestations of solar cycle. They are associated with absence of spots on the Sun in the northern and southern hemispheres at different intervals. This phenomenon is defined as anti-cycle of solar activity. Properties of discreteness of anti-cycles are presented in this paper on "spotless days’ periods". On their basis the appropriate monthly and annual data was received. The basic characteristics of the manifestations of the discreteness of activity anti-cycles had been determined. It noted the «switch effect» of the existence of the solar dynamo. It manifests itself in the rapid transition from a regime of «spotless days» to the regime of continuous generation.